ANALISIS PELAKSANAAN PELAYANAN KESEHATAN PASIEN PADA PUSKESMAS KECAMATAN LUBUK DALAM KABUPATEN SIAK - Sofiyah, Yuliana; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Health services is a factor affecting the degree of public health, because of the existence of health facilities able to determine service the recovery of health, the prevention of a disease, treatment and nursing as well as groups and societies who need services – the health services. This study was conducted at the clinic Lubuk Dalam in Siak regency located in road Puskemas Rawang Kao Lubuk Dalam subdistrict in Siak regency. Purpose of this research is to analyze the performance of health services patients at the clinic .In this study the methodology used is descriptive analysis, where the sampel that is used visitors of public health centers and as source information is the administration, to determine the samples using the formula Slovin, accidental sampling method with sampling, stratified random sampling for the service, data collection techniques through observation, interviews, and questionnaires.From the analysis of the performance of health services performed by the clinic include speed, accuracy, friendliness, comfort stating that service activities are on good category.Keywords : service, health services, public health center